2020
DOI: 10.20965/ijat.2020.p0959
|View full text |Cite
|
Sign up to set email alerts
|

Durability Evaluation of an Additive Manufactured Biodegradable Composite with Continuous Natural Fiber in Various Conditions Reproducing Usage Environment

Abstract: Recently, biodegradable plastic materials that can be decomposed by living organisms have attracted significant attention because of the great demand for the safe disposal of plastics. Recycling has failed to provide a practical solution for plastic waste disposal (60% of all plastics produced are discarded). It is difficult to achieve both durability and biodegradability in biodegradable plastics. In additive manufacturing processes, polylactic acid (PLA), one of the biodegradable plastics, is typically used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The main conclusion of this study was that even though carbon fiber composites have better mechanical performance than jute composites, the latter has better mechanical resistance than the neat PLA specimens. Hemp fiber was evaluated as PLA reinforcement by Yacuchi et al [ 150 ] According to the obtained results, hemp/PLA composites exhibited an increase in tensile strength from 46.8 MPa to 65.3 MPa compared to the neat PLA matrix. Meanwhile, They identified that the composite specimens deteriorate faster than the PLA.…”
Section: Sustainable Materials For 3d Printing: Giving Value To Wastementioning
confidence: 99%
“…The main conclusion of this study was that even though carbon fiber composites have better mechanical performance than jute composites, the latter has better mechanical resistance than the neat PLA specimens. Hemp fiber was evaluated as PLA reinforcement by Yacuchi et al [ 150 ] According to the obtained results, hemp/PLA composites exhibited an increase in tensile strength from 46.8 MPa to 65.3 MPa compared to the neat PLA matrix. Meanwhile, They identified that the composite specimens deteriorate faster than the PLA.…”
Section: Sustainable Materials For 3d Printing: Giving Value To Wastementioning
confidence: 99%
“…The SA algorithm uses an alternate process to reach a state of quasi-thermodynamic equilibrium, and its main feature is that it allows hill-climbing (i.e., movement that worsens the value of the objective function), a process that makes it partial minima at higher temperatures, thus avoiding falling into a local optimum [7]. The main components of the SA algorithm are.…”
Section: Sa Algorithmmentioning
confidence: 99%
“…Under this condition, the displaced ball filler of the displaced biochemical pond which has been successfully cultivated with biofilm and operated stably for 1 month is taken, and the bacteria film on the surface of the displaced ball shell and the surface of the internal volcanic rock particles are scraped off a little and transferred to the anaerobic medium for cultivation for a period of time. After a period of incubation, the microorganism survival in the medium was observed by microscopic examination; the total length of the displaced biochemical pond was about 50 cm, and a number of displaced ball fillers were taken every 10 cm from the inlet, totaling 5 sections, and the microorganism species in different flow sections of the displaced biochemical pond were analyzed by microscopic examination, so as to understand the operation mechanism of the displaced ball fillers in reducing sludge volume in the wastewater treatment process [14,15].…”
Section: Displacement Ball Packing Sludge Reduction Mechanismmentioning
confidence: 99%